2020
DOI: 10.1093/mnras/staa1293
|View full text |Cite
|
Sign up to set email alerts
|

Photoionizing feedback in spiral arm molecular clouds

Abstract: We present simulations of a 500 pc2 region, containing gas of mass 4 × 106 M⊙, extracted from an entire spiral galaxy simulation, scaled up in resolution, including photoionizing feedback from stars of mass >18 M⊙. Our region is evolved for 10 Myr and shows clustered star formation along the arm generating ≈ 5000 cluster sink particles ≈ 5 per cent of which contain at least one of the ≈ 4000 stars of mass >18 M⊙. Photoionization has a noticeable effect on the gas in the region, producing ionized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 88 publications
1
58
2
Order By: Relevance
“…We use the smoothed particle hydrodynamics code NG, which originated with Benz et al (1990) and Benz (1990), and was substantially modified by Bate et al (1995) and Price & Monaghan (2007). Full details of the initial conditions and cluster-sink particle setup can be found in Bending et al (2020) -we provide a summary here.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We use the smoothed particle hydrodynamics code NG, which originated with Benz et al (1990) and Benz (1990), and was substantially modified by Bate et al (1995) and Price & Monaghan (2007). Full details of the initial conditions and cluster-sink particle setup can be found in Bending et al (2020) -we provide a summary here.…”
Section: Methodsmentioning
confidence: 99%
“…This evolved for about 300 Myr with a mass resolution of 312.5 M per particle, and included self-gravity, ISM heating/cooling, H 2 and CO chemistry, and injections of energy representing supernova events (Dobbs et al 2011). Bending et al (2020) extracted a section of a spiral arm with dimensions ∼ 500 × 500 × 100 pc and mass 4 × 10 6 M (named 'SR' in that paper). They also enhanced the resolution to 1 M per particle, permitting the creation of cluster-sink particles for tracking star formation.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age range observed for the clusters within the H ii regions is in agreement with studies of YSCs in local galaxies (Whitmore et al 2011;Hollyhead et al 2015;Hannon et al 2019;Grasha et al 2019), that find that clusters emerge from their natal gas in <4−5 Myr, but that the process can start as early as 2−3 Myr. Also simulations of cluster formation including solely the effect of photoionisation and stellar winds (Dale et al 2014;Bending et al 2020), have shown that within 3 Myr, and before the onset of SN, several clusters have vacated some channels with low gas density. These channels are easily ionised; therefore ionising radiation can escape from the H ii regions even if star formation is still taking place.…”
Section: Yscs Age Mass and Ionising Flux Distributionmentioning
confidence: 99%